Integrating platelet-rich plasma therapy into nursing practice: a review of biological mechanisms and clinical applications - He, Jing; Wang, Darong (Frontiers in Bioengineering and Biotechnology, 2026)
Platelet-rich plasma (PRP) therapy, an autologous biologic rich in growth factors, has emerged as a promising modality in regenerative medicine, with expanding relevance in nursing-led care. PRP promotes tissue regeneration, modulates inflammation, and enhances functional recovery in several conditions, including chronic wounds, musculoskeletal disorders, and aesthetic applications. Its minimally invasive nature and patient-specific approach align closely with holistic nursing models. This review synthesizes current evidence on the biological mechanisms underlying PRP activity, including platelet composition, growth factor signaling, and immunomodulation, and critically evaluates clinical outcomes relevant to nursing practice. Particular attention is given to nursing roles throughout the PRP treatment continuum, from patient selection and preparation to monitoring and long-term follow-up. Despite its clinical promise, PRP adoption in nursing practice faces barriers such as formulation variability, lack of standardized protocols, and limited nurse-led guidelines. We propose strategic directions for integrating PRP into evidence-based nursing frameworks, emphasizing digital tools, individualized care pathways, and interdisciplinary collaboration.